THE EFFECTIVENESS OF TEACHER INDIRECT FEEDBACK IN IMPROVING STUDENTS' WRITING SKILL IN WRITING RECOUNT TEXTS - Dewi, Bintang Permata (2016)
This study examines the effectiveness of teacher indirect feedback in improving students' writing in writing recount text. The objective of this study is to find out whether teacher written indirect feedback is effective to improve students' ability in writing recount text or not. Also, it intends to see the students' responses toward the use of teacher written indirect feedback in teaching recount text. The design used is the quasi-experimental design involving sixty students of X IIS 1 and X IIS 2 at SMAN 15 Bandung as the sample of this research. The instruments used are Writing Assessment Measurement (WAM), originally designed by Wechsler Objective Language Dimensions (WOLD, Psychological Corporation, 1996), and the questionnaire of the effectiveness of teacher indirect feedback. Writing Assessment Measurement is used to discover that teacher feedback by using indirect written feedback strategy can improve students' ability in writing recount text. The result of this study that there is a significant difference between students' last draft scores in the teacher written indirect feedback group and the teacher oral indirect feedback group. Most students tended to respond positively toward the use of written feedback provided by the teacher and they considered it helpful for them to make a better writing. As a result, it can be concluded that the implementation of teacher indirect feedback is effective in improving students' writing skill in writing recount text.;--- Penelitian ini menginvestigasi efektivitas umpan balik tidak langsung dari guru secara tertulis dalam meningkatkan kemampuan menulis siswa dalam menulis teks recount. Tujuan dari penelitian ini adalah untuk mengetahui apakah umpan balik tertulis secara tidak langsung dari guru dalam meningkatkan kemampuan menulis siswa dalam menulis teks recount efektif atau tidak. Penelitian ini juga memiliki tujuan untuk mengetahui respon siswa terhadap penerapan umpan balik tertlusi secara tidak langsung dari guru dalam pembelajaran teks recount. Desain penelitian yang digunakan yaitu penelitian eksperimental semu yang melibatkan 60 siswa kelas X IIS 1 dan X IIS 2 di SMAN 15 Bandung yang dipilih sebagai sampel penelitian. Instrumen yang digunakan yaitu Writing Assessment Measurement (WAM), yang didesain oleh Wechsler Objective Language Dimensions (WOLD, Psychological Corporation, 1996), dan instrumen kedua yaitu kuesioner penggunaan umpan balik tidak langsung. Writing Assessment Measurement digunakan untuk mengetahui umpan balik dari guru dengan menggunakan strategi umpan balik tidak langsung dapat meningkatkan kemampuan siswa dalam menulis teks recount. Hasil dari penelitian ini menunjukan bahwa adanya perbedaan yang signifikan antara hasil akhir kelompok dengan umpan balik tertulis secara tidak langsung dari guru dan kelompok dengan umpan balik verbal secara tidak langsung dari guru. Sebagian siswa merespon secara positif terhadap penggunaan umpan balik tidak langsung dari guru secara tertulis dan siswa-siswa menyadari bahwa hal tersebut sangat membantu dalam memperbaiki tulisan mereka. Hasil penelitian ini menunjukan bahwa penerapan umpan balik tidak langsung dari guru adalah efektif dalam meningkatkan kemampuan menulis siswa dalam menulis teks recount.